Knowledge production process together: research group in the process of creation - Salles, Cecilia Almeida (Farol, 2023)
The purpose of this article is to reflect on the Creation Processes Research Group at PUCSP, with a focus on a new approach to learning how to produce together, particularly as a result of the impositions of prolonged isolation during the Covid-19 pandemic. In order to do this, a historical contextualization of the group was carried out, marked by some defining moments in the broadening of directions and expansion of studies in this area. The result reveals the importance of the group’s trajectory in taking the process of creation as a major purpose, supported by a critical theory.